MODERN CONSTRUCTION SOLUTIONS FOR PRESTRESSED CABLE DOMES AND WAYS TO IMPROVE THEM (Collection of scientific works «Modern structures of metal and wood», 2021)
To  create  fundamentally  new  innovative  large-span  structures  of  buildings  and structures coverings, modern design solutions of prestressed cable domes of the Tensegrity type are considered. The service life of the first built Tensigrity domes is only 35 years. These are fairly new, effective structures that require careful study and use of modern scientific approaches for their design using software systems, since their work under load and the construction process are quite complex. The design analysis and erection of self-stressed structures is based on the invention of an equilibrium structure, the so-called tensegrity form. The search for the shape is multidimensional and consists of the stage of computational analysis of a self-stressed dome for the equilibrium position of elements and their nodes, selection of the most stable and rigid structure, as well as taking into account possible unfavorable  loads  during  operation  and  the  initial  load  in  the  elements  from  the  application  of prestressing. To determine the shape of cable domes, a nonlinear programming problem with given axial forces is formulated, which can be considered as the problem of minimizing the difference in the  total  strain  energy  between  the  elements  of  the  cables  and  struts  under  constraints  on  the compatibility conditions. The first step in calculating the prestressing of a cable dome is to assess the feasibility of its geometry. The possibility of forming a cable dome of negative Gaussian curvature is considered  and  a  method  for  calculating  the prestressing  for  this  new  shape  is  investigated.  The proposed method is effective and accurate in determining the allowable prestressing for a cable dome with negative Gaussian curvature and can be used for other types of prestressed structures. The new directions  for  the  development  of  effective  constructive  solutions  for  large-span  coatings  are presented, including a suspended-dome structure, which combines the advantages of a mesh shell and a cable dome. Special attention should be paid to experimental studies on models of tensegrity domes, the results of which demonstrate the positive and negative aspects of the behavior of structures under load, the process of their erection, as well as the possibility of control and restoration during operation.